Stem Cell Factor Expression after Renal Ischemia Promotes Tubular Epithelial Survival - Stokman, Geurt; Stroo, Ingrid; Claessen, Nike; Teske, Gwendoline J. D.; Weening, Jan J.; Leemans, Jaklien C.; Florquin, Sandrine (PloS one, 2010)
Renal ischemia leads to apoptosis of tubular epithelial cells and results in decreased renal function. Tissue repair involves re-epithelialization of the tubular basement membrane. Survival of the tubular epithelium following ischemia is therefore important in the successful regeneration of renal tissue. The cytokine stem cell factor (SCF) has been shown to protect the tubular epithelium against apoptosis. In a mouse model for renal ischemia/reperfusion injury, we studied how expression of c-KIT on tubular epithelium and its ligand SCF protect cells against apoptosis. Administration of SCF specific antisense oligonucleotides significantly decreased specific staining of SCF following ischemia. Reduced SCF expression resulted in impaired renal function, increased tubular damage and increased tubular epithelial apoptosis, independent of inflammation. In an in vitro hypoxia model, stimulation of tubular epithelial cells with SCF activated survival signaling and decreased apoptosis. Our data indicate an important role for c-KIT and SCF in mediating tubular epithelial cell survival via an autocrine pathway.